2017
DOI: 10.1042/bsr20170779
|View full text |Cite
|
Sign up to set email alerts
|

α-Mangostin protects against high-glucose induced apoptosis of human umbilical vein endothelial cells

Abstract: Diabetic vascular complications result from high-glucose induced vascular endothelial cell dysfunction. There is an emerging need for novel drugs with vascular endothelial cell protective effects for the treatment of diabetic vascular complications. The present study aimed to investigate the protective effect of α-mangostin against high-glucose induced apoptosis of cultured human umbilical vein endothelial cells (HUVECs). HUVECs were treated with glucose to induce apoptosis. The expression of the apoptosis-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 44 publications
(45 reference statements)
1
23
0
Order By: Relevance
“…Importantly, supplementation of α-MG partially maintained the balance between Bax and Bcl-2, resulting in the prevention of mitochondrial dysfunction caused by APAP. In fact, our results were supported by a recent reports by Luo et al, who reported that α-MG exerted anti-apoptotic effects on high-glucose-induced vascular endothelial cell dysfunction via upregulation of Bcl-2 and downregulation of Bax protein expression [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, supplementation of α-MG partially maintained the balance between Bax and Bcl-2, resulting in the prevention of mitochondrial dysfunction caused by APAP. In fact, our results were supported by a recent reports by Luo et al, who reported that α-MG exerted anti-apoptotic effects on high-glucose-induced vascular endothelial cell dysfunction via upregulation of Bcl-2 and downregulation of Bax protein expression [ 40 ].…”
Section: Discussionsupporting
confidence: 90%
“…After that, we detected the aSMase activity, ceramide content, eNOS expression, NO production and vascular function. Desipramine is able to inhibit aSMase activity and ceramide accumulation 8,23‐25 . Here, we used desipramine as an aSMase inhibitor control in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The cells were seeded in a six-well plate and received different treatments, such as NC (normal control, 5 mM D-glucose), HG (high glucose, 25 mM D-glucose), LG (L-glucose, 25 mM L-glucose + 5 mM D-glucose), DES (desipramine, 10 μM). The desipramine concentrations used were based on our previous study [14].…”
Section: Methodsmentioning
confidence: 99%